Literature Review: Regarding Stock Returns in Initial Public Offerings - Condro Widodo; R. Muh Syah Arief Atmaja Wijaya; Arief Budiman; Vicky Vendy; Diarany Sucahyati; Muhammad Aditya Bahruna; Farrel Sabililillah; Alifia Putri P. (Future Science, 2023)
This research aims to conduct a literature review of previous research on factors that influence stock returns at the time of an IPO. This literature review uses nine articles from 2017-2022 in the journal database. This literature review finds factors influencing stock returns during initial public offerings, intellectual capital disclosure, company growth opportunities, research and development (R&D), underwriter reputation, market conditions, percentage of shares offered, and profitability. Future researchers should enrich the journal database further for perfect literature reviews.